Microplasma assisted synthesis of silver nanoparticles capped with PVA, PVP and Sucrose. (17th June 2021) - Saleem, Muhammad Taimoor; Bashir, Shazia; Bashir, Muhammad
Abstract: Silver nanoparticles (Ag NPs) have been synthesized by exposing Ar gas microplasma to liquid solution containing Ag + ions. Sucrose, Polyvinyl Alcohol (PVA) and Polyvinylpyrrolidone (PVP) were added separately as capping agents in aqueous solution to avoid agglomeration of Ag NPs. There are two main mechanism involved in this experiment (1). interaction of electrons from microplasma with Ag + ions present in aqueous solution and (2). Control of Ag NPs size by capping agents by surrounding Ag NPs. We have performed a comparison of capping performance of Sucrose and PVA in terms of stability of Ag NPs with the help of Ultraviolet-Visible spectroscopy (UV-vis). X-ray diffraction (XRD) analysis of Ag NPs capped with PVA and Sucrose shows average crystal size of 25 nm and 60 nm respectively. Dynamic Light Scattering (DLS) analysis was employed to measure the size distribution of Ag NPs capped with Sucrose, PVA and PVP capping agents. DLS showed that PVA-capped Ag NPs formed are more uniform in size as compared to Sucrose-capped. Average size of Ag NPs measured from DLS is 65 nm when capped with PVA and 120 nm when capped with Sucrose. Fourier Transform Infrared Spectroscopy (FTIR) spectrum obtained have bands of wavenumbers corresponding to functional groups of Sucrose and PVA which are present around Ag NPs.